ICT, Development and Young People. A State of the Art. - Padilla de la Torre, María Rebeca (2019)
The present article is an international review or state of the art that analyzed more than seventy texts of studies and interventions of information and communication technologies for development and social change with the objective of identifying tendencies, in particular those that had the specific purpose of youth development. In the results of this systematization stands out the discussions around the concept of development, the predominance of works in marginalized communities, and the need to orient this field towards situated users and problems, as is the case of young people, a topic that has been less attended.